MEKANISME CORPORATE GOVERNANCE INTERNAL DAN KECENDERUNGAN MANAJER UNTUK BERPERILAKU OPORTUNISTIK - H. Umar Mai (Faculty of Economics and Business Universitas Jenderal Soedirman, 2010)
This study aims to determine and analyze the influence of internal corporate governance mechanisms of the tendency of managers to behave opportunistically. Samples used are manufacturing companies listed in Indonesia Stock Exchange with the observation period started in 2000 to 2007, and data analysis methods used are the path analysis through Amos 1.6 program. The results of this study show that: 1) internal corporate governance mechanisms that represented with independent boards and boards size could prevent the tendency of managers to opportunistic behavior represented by debt to assets ratio; 2) the internal mechanisms of corporate governance represented by boards size are able to prevent the tendency of managers to behave opportunistic represented with systematic risk.